Analisis Kepuasan Pelanggan Terhadap Kualitas Pelayanan Pramusaji Restoran Thong Inn Hotel Di Kabupaten Deli Serdang - Siregar, Mhd Daud (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2025)
This research examines customer satisfaction with the quality of waiter service at the Thong Inn Hotel Restaurant, Deli Serdang Regency. Customer loyalty and hotel reputation are influenced by the pleasant experience provided through high-quality service. The research used a quantitative descriptive methodology with 80 respondents. Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) were used to analyze the data. The IPA results show that several elements of tangibility, dependability, responsiveness, empathy and assurance have met consumer expectations, with some being in Quadrant I (improvement priorities) and Quadrant II (maintain performance). However, aspects such as product/menu knowledge and menu information still require improvement. CSI data shows that the level of customer satisfaction reaches 81%-100%, categorized as Very Happy. Based on the survey, restaurant management is advised to maintain friendliness and responsiveness in service, as well as improve aspects such as processing special requests and speed of service. This focus on improvement is expected to increase overall customer satisfaction. This will ultimately have a positive impact on customer loyalty, patronage and reputation of restaurants and hotels in the future. This research highlights the importance of high-quality service as a key factor in creating positive experiences for customers and driving business sustainability.